Human IgG antibody profiles differentiate between symptomatic patients with and without colorectal cancer. Issue 1 (13th October 2009) - Kijanka, G; Hector, S; Kay, E W; Murray, F; Cummins, R; Murphy, D; MacCraith, B D; Prehn, J H M; Kenny, D
Abstract : Objective: Patients with cancer have antibodies against tumour antigens. Characterising the antibody repertoire may provide insights into aberrant cellular mechanisms in cancer development, ultimately leading to novel diagnostic or therapeutic targets. The aim of this study was to characterise the antibody profiles in patients whose symptoms warranted colonoscopy, to see if there was a difference in patients with and without colorectal cancer. Methods: Patients were recruited from a colonoscopy clinic. Individual serum samples from 43 patients with colorectal cancer and 40 patients with no cancer on colonoscopy were profiled on a 37 830 clone recombinant human protein array. Antigen expression was evaluated by quantitative reverse transcription-PCR and by immunohistochemistry on tissue microarrays. Results: Using a sex- and age-matched training set, 18 antigens associated with cancer and 4 associated with the absence of cancer (p<0.05) were identified and confirmed. To investigate the mechanisms triggering antibody responses to these antigens, antigen expression was examined in normal colorectal mucosa and colorectal carcinoma of the same patients. The identified antigens showed cellular accumulation (p53), aberrant cellular expression (high mobility group B1 (HMGB1)) and overexpression (tripartite motif-containing 28 (TRIM28), p53, HMGB1, transcription factor 3 (TCF3), longevity assurance gene homologue 5 (LASS5) and zinc finger protein 346 (ZNF346)) in colorectal cancer tissue compared with normal colorectal mucosa. Conclusions: It is demonstrated for the first time that screening high-density protein arrays identifies unique antibody profiles that discriminate between symptomatic patients with and without colorectal cancer. The differential expression of identified antigens suggests their involvement in aberrant cellular mechanisms in cancer.